Analisador robótico para determinações físicoquímicas no controle de qualidade de águas - Almeida Júnior, Pedro Lemos de (2019)
Water quality has been increasingly studied. This should be related to the management of anthropogenic residues and especially their progressive scarcity. In this context was proposed a robotic for conductivity, pH, total alkalinity, total hardness, chloride, nitrite, total reactive phosphorus and total iron analysis in commercial mineral waters samples. The ATLAS analyzer comprises a syringe pump coupled to a robotic arm, a solution holder, a plate and a reactor plate, conductivity, temperature and a colorimetric sensor (adapted from webcam). The analyzer is controlled by a software able to process data from sensors, automatic calibrations and calculations of analytical results. ATLAS can measure the conductivity and automatically calculate a sensor constant. It is calibrated to determine the pH from the variation of a "universal" indicator according to the Hue parameter from digital images of the reactor. Through its programming, ATLAS also monitors the operations in automatic sequences of suppression of digital filming and constructs analytical curves from the color standard in the colorimetric analyzes. The analyzer was applied in mineral water analysis and its results do not present statistical differences from the reference methods. In addition, as measured conductivity and pH, the analytical frequencies of 344 and 166 analyzes h -1, respectively. The titrimetric analysis returned the analytical frequency, between 112 and 92 analyzes h-1, and generated a total of 99.4% less residues than those generated using the reference methods. The colorimetric analysis presents analytical frequencies, between 72 and 83 analyzes h-1 and detection limits of 1.26 μg L-1, 6,79 μg L-1 and 460 μg L-1, for quantification of nitrite, total reactive phosphorus and total iron, respectively. In this way, the ATLAS analyzer presents itself as an unprecedented tool, with high precision and accuracy, low cost and with low waste generation, for multi-parameter analysis of commercial bottled waters.